Antagonism Test Of Isolate Normal Flora On Palms Against Staphylococcus Aureus And Staphylococcus Epidermis: Staphylococcus Aureus - Rizka Efi Mawli; Devi Anggraini Putri; Dwi Aprilia Anggraini (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: The body's normal flora is a form of the body's defense against initial infection, namely the attachment and multiplication of pathogenic bacteria. This research aims to examine the antagonistic of the normal flora in human palm against Staphylococcus aureus and Staphylococcus epidermis. Methods: This research consisted of two steps. Step I. Isolation of normal flora bacteria on human palms and Step II is Antagonistic test between normal flora isolates against Staphylococcus aureus and Staphylococcus epidermis which carried out separately using disc diffusion to determine the diameter of the inhibition zone formed. Results: A total of 8 isolates were successfully isolated and 4 of them were able to form an inhibition zone against the test bacteria. Conclusion: MB1.2 isolate is the most potential for further research as an antagonism antibacterial agent against Staphylococcus aureus and Staphylococcus epidermis.